Krisis Ekologis di Tagulandang “Muliku Wanua” Suatu Upaya Mengatasi Krisis Ekologis di Tagulandang - Vonny Vallentin Makinggung; Richard A.D. Siwu; Anita I. Tuela (Peneliti.net, 2021)
The purpose of the study this is to examine the crisis of ecology that occurred in Tagulandang and analyze the things that lead to the problem of ecology in Tagulandang. This is a qualitative research with descriptive-comparative method, held in Tagulandang, Siau Tagulandang Biaro Regency, in the year of 2021. Data were collected through activities of observations and interviews as well as the literature research. From the results of data analysis and interpretation, it was found that (1). There was an ecological crisis in Tagulandang; (2). The paradigm of anthropocentrism affect the treatment of the Tagulandang society towards the environment, which resulted the relationship of man and nature become damaged. Humans are seen as subjects and nature becomes objects that are exploited , damaged and there is no action for nature care and preservation ; (3). Local Wisdom, Muliku Wanua is the heritage of culture that can raise communities awareness of ecologica lin Tagulandang to develop harmony with nature. From the results of the findings, then the people of Tagulandang need to fix the thinking paradigm over the nature of the universe which is the creation of God . The relation between man and nature is a relation which emphasizes the understanding of the integrity of creation so the relation of nature and humans becomes harmonious. Local wisdom ,muliku wanua is the value of the cultural of the Tagulandang community that can build ecological awareness so it can improve the paradigm and treatment of the people Tagulandang towards nature in order to be better.